Aberrant root formation - An unreported complication of dental trauma - V Revathy; R Abirami; R Abharna (Wolters Kluwer Medknow Publications, 2018)
Trauma and infection to immature teeth can result in a number of complications. Discontinuity in the formation of root is one such complication which has never been documented before. In the following article, a case report of this aberrancy which was observed in the root of a permanent central incisor, subsequent to a traumatic injury is discussed. In spite of this discontinuity, complete root formation and vital pulp were noted in the tooth. Since such a case has not been reported in literature till date, this complication is described and the possible cause of its occurrence is discussed in this article.